2015
DOI: 10.1007/s13361-015-1109-y
|View full text |Cite|
|
Sign up to set email alerts
|

Large-Scale Examination of Factors Influencing Phosphopeptide Neutral Loss during Collision Induced Dissociation

Abstract: Collision-induced dissociation (CID) remains the predominant mass spectrometry based method for identifying phosphorylation sites in complex mixtures. Unfortunately, the gas-phase reactivity of phosphoester bonds results in MS/MS spectra dominated by phosphoric acid (H3PO4) neutral loss events, suppressing informative peptide backbone cleavages. To understand the major drivers of H3PO4 neutral loss, we performed robust non-parametric statistical analysis of local and distal sequence effects on the magnitude an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…It was noticeable that indeed, the majority (>70%) of phosphopeptides containing confidently localised pHis or pTyr (ptmRS>99%), were observed with no neutral loss, although this was not as marked for pSer/Thrcontaining peptides, where only 30% of peptides across all SAX fractions exhibited no neutral loss. These findings agree with previous observations demonstrating that phosphopeptide neutral loss propensity is dependent on both the type and relative position of amino acids within the sequence [42][43][44] . Further examination of the neutral loss ions (∆80 amu vs ∆98 amu vs ∆116 amu) revealed that the nature of the phosphorylated residue had very little effect on the likelihood of observation of a ∆80 amu ion from the precursor following HCD ( Fig.…”
Section: Precursor Neutral Loss Ions Do Not Improve Confidence In Idesupporting
confidence: 93%
“…It was noticeable that indeed, the majority (>70%) of phosphopeptides containing confidently localised pHis or pTyr (ptmRS>99%), were observed with no neutral loss, although this was not as marked for pSer/Thrcontaining peptides, where only 30% of peptides across all SAX fractions exhibited no neutral loss. These findings agree with previous observations demonstrating that phosphopeptide neutral loss propensity is dependent on both the type and relative position of amino acids within the sequence [42][43][44] . Further examination of the neutral loss ions (∆80 amu vs ∆98 amu vs ∆116 amu) revealed that the nature of the phosphorylated residue had very little effect on the likelihood of observation of a ∆80 amu ion from the precursor following HCD ( Fig.…”
Section: Precursor Neutral Loss Ions Do Not Improve Confidence In Idesupporting
confidence: 93%
“…10 On the other hand, the phosphopeptide systems studied by Cui and Reid exhibited high transfer ratios (approximately 50 times greater than average), 12 which beg the question what mechanism may be at play, and how general this mechanism may be. Surprisingly, the mechanistic study of phosphoric acid (H 3 PO 4 ) neutral loss 6,[15][16][17][18][19][20] has generated much more interest than has the mechanism for phosphosite scrambling. The only proposed mechanism for phosphate group transfer has cited the strong hydrogen bonding between the phosphate group and the protonated arginine side chain as a stabilizing factor allowing for the concerted transfer of the phosphate group and hydroxy hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Negative polarity peptide analysis generally results in uninformative CID mass spectra comprised mostly of neutral phosphate losses, precluding both identification and characterization of peptides. 12,13 Ultraviolet photodissociation (UVPD) using 193 nm photons is an alternative to existing collision- and electron-based activation methods that offers several advantages for phosphorylation site mapping in the CTD. Charge state bias, which is a limitation for traditional methods, is largely overcome using UVPD, and high sequence coverage has been demonstrated even for singly charged precursor ions.…”
mentioning
confidence: 99%